Accountant-general department: Empowering public sector finance through data analytics in Singapore - PAN, Gary (Institutional Knowledge at Singapore Management University, 2019)
In June 2018, Ow Fook Chuen, the Accountant-General of the Accountant-General’s Department (AGD), was in charge of the Accountant-General’s Department (AGD) as it sought to improve through innovation and the use of technology. Being the steward of public sector finance transformation, AGD partnered public sector agencies to uplift the role of finance from being the custodian of public finance, to a strategic partner who empowers decision-making. In its role, AGD had to handle various financial transactions related to the government and its vendors, and process the payroll of all government officers. Staff from AGD were seconded to work closely with other public sector finance professionals in the finance and internal audit departments of various public sector agencies in order to implement key initiatives. To improve the accuracy and efficiency of its processes, AGD had reviewed new technologies and spoke to private sector companies on their experiences. It linked many individual systems used by various ministries across the Whole-of-Government (WOG) into a central data analytics platform to enable public sector agencies to perform their jobs more effectively and efficiently. Despite facing a few challenges, Ow knew that the data analytics journey would help AGD strengthen finance functions across WOG.